Development and evaluation of a health education module for the prevention of respiratory tract infections among private hajj and umrah pilgrims - Goni, Mohammed Dauda (2020)
Hajj pilgrimage is usually associated with a regular occurrence of respiratory tract infection among pilgrims. Vaccination uptake and other preventive behaviours have generally been low among pilgrims across the globe. Despite this, there is presently no validated health theory-based health education module in Malaysia to guide the pilgrims on how to boost compliance with these preventive practices and increase their knowledge towards respiratory tract infection, preventive attitudes and practices towards prevention strategies. The general objective of this study is to develop and evaluate the effectiveness of health education modules against respiratory tract infections among Hajj pilgrims from Malaysia. This study was carried out in phases comprising of development and validation of questionnaire phase, development and validation of health education module for respiratory tract infection prevention phase, baseline characterization of pilgrims’ phase, intervention phase and evaluation phase. At the first phase of the study, a cross-sectional study was conducted for the development and validation of a measurement tool using the content, construct (items response theory, exploratory factor analysis and confirmatory factor analysis) validation and reliability. This phase is followed by the development and validation of new health education module via a smartphone application. For the intervention and the evaluation phase, a quasi-experimental study was utilized, where pre-post intervention data were analysed among 52 and 50 Hajj/Umrah pilgrims in the intervention or control group respectively. The intervention group was given health education module on the prevention of respiratory tract infections during Hajj and Umrah in the form of a smartphone application which was strictly guided by the health belief model. The control group received a smartphone application on normal Hajj and Umrah guidance from a different Hajj/Umrah travel company. Follow-up data were collected using the same questionnaire that was used during the pre-test data collection. Mixed design repeated measure ANOVA was used to analyse the effect of group, time, and group-time interaction on the dependent variables. There was a significant improvement in knowledge score and the main effect in the intervention group compared to the control group, based on time (p = 0.005, ηp2 = 0.075). Likewise, there was significant improvement in attitude score and main effect based on time (p = 0.035, ηp2 = 0.044). Similarly, there was a significant change in practice score and also main effect based on time (p = <0.001, ηp2 = 0.155) and interaction of group with time (p = 0.042, ηp2 = 0.041). Similarly, the occurrence of RTI in the intervention group is lower when compared to the control group. The new health educational intervention module developed was effective in improving the knowledge, attitude and practices toward prevention of RTI among Hajj pilgrims from Malaysia. Further studies are also needed to investigate the barriers and motivators to link the knowledge gap about the uptake of mandatory and recommended vaccine as well as the other components of the module. Therefore, Hajj agencies need to conduct health education before departure of pilgrims to prepare them against the common respiratory infections or in the event of outbreaks of infection during Hajj/Umrah.